The clinical significance of sub-total surgical resection in childhood medulloblastoma: a multi-cohort analysis of 1100 patients - Claire Keeling; Simon Davies; Jack Goddard; Vijay Ramaswamy; Ed C. Schwalbe; Simon Bailey; Debbie Hicks; Steven C. Clifford (2024)
BackgroundMedulloblastoma patients with a sub-total surgical resection (STR; >1.5 cm2 primary tumour residuum post-surgery) typically receive intensified treatment. However, the association of STR with poor outcomes has not been observed consistently, questioning the validity of STR as a high-risk disease feature.MethodsWe collected extent of resection (EOR) data from 1110 patients (from UK CCLG centres (n = 416, collected between September 1990 and July 2014) and published (n = 694) cohorts), the largest cohort of molecularly and clinically annotated tumours assembled to specifically assess the significance of EOR. We performed association and univariable/multivariable survival analyses, assessing overall survival (OS) cohort-wide and with reference to the four consensus medulloblastoma molecular groups and clinical features.FindingsSTR was reported in 20% (226/1110) of patients. Non-WNT (p = 0.047), children <5 years at diagnosis (p = 0.021) and metastatic patients (p < 0.0001) were significantly more likely to have a STR. In cohort-wide analysis, STR was associated with worse survival in univariable analysis (p < 0.0001). Examination of specific disease contexts showed that STR was prognostic in univariate analysis for patients receiving cranio-spinal irradiation (CSI) and chemotherapy (p = 0.016) and for patients with Group 3 tumours receiving CSI (p = 0.039). STR was not independently prognostic in multivariable analyses; outcomes for patients who have STR as their only risk-feature are as per standard-risk disease. Specifically, STR was not prognostic in non-metastatic patients that received upfront CSI.InterpretationIn a cohort of 1100 molecularly characterised medulloblastoma patients, STR (n = 226) predicted significantly lower OS in univariable analysis, but was not an independent prognostic factor. Our data suggest that maximal safe resection can continue to be carried out for patients with medulloblastoma and suggest STR should not inform patient management when observed as a sole, isolated risk-feature.FundingCancer Research UK, Newcastle Hospitals Charity, Children's Cancer North, British Division of the International Academy of Pathology.